Method for improving stability of sulfide electrolyte to lithium on large scale
By immersing the sulfide electrolyte in liquid inorganic metal halide under the protection of inert gas and mechanically combining it, the composite sulfide electrolyte is prepared, which solves the problem of unsatisfactory matching of sulfide electrolyte and lithium metal, and achieves high stability of lithium and improved battery performance.
Patent Information
- Application Number
- CN202510130557.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2045-02-06
AI Technical Summary
The mutual matching between the sulfide solid electrolyte and lithium metal is not ideal, causing lithium metal to penetrate into the electrolyte, destroying the brittle electrolyte layer, thereby affecting the cycle life and magnification capacity of the battery.
By immersing the sulfide electrolyte in liquid inorganic metal halide under the protection of an inert gas and performing mechanical recombination, a composite sulfide electrolyte is prepared. The electrolyte has high ionic conductivity and high density, and can react with metal lithium to form a self-limiting growth interface layer, thereby enhancing the diffusion rate of lithium in the interface.
It significantly improves the stability of lithium, extends the cycle life of all-solid lithium metal batteries, and improves the rate performance.
Smart Images

Figure CN119569005A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solid electrolyte materials for lithium metal batteries, and in particular relates to a method for improving the stability of sulfide electrolytes to lithium on a large scale. Background Art
[0002] As the mainstream technology of secondary batteries, lithium-ion batteries are widely used in scenarios such as electric vehicles, mobile communication equipment energy storage, and large-scale power energy storage to achieve clean energy development. However, due to their limited ultimate energy density, lithium-ion batteries have gradually failed to meet the requirements of energy storage systems for new-generation electronic devices. In addition, the safety of traditional lithium-ion batteries has been criticized due to the risks of leakage, combustion, and explosion of the organic electrolytes used.
[0003] All-solid-state lithium metal batteries are widely considered to be the most promising technical route to solve the above problems. At present, the solid electrolytes used in all-solid-state lithium batteries can be mainly divided into two categories: inorganic solid electrolytes and polymer solid electrolytes. Among all solid electrolytes, sulfide electrolytes are regarded as one of the most promising electrolyte materials for industrialization due to their high ionic conductivity and high processability. At present, all-solid-state lithium metal batteries using sulfide solid electrolytes have become the research focus of academia and industry. However, the mutual matching between sulfide solid electrolytes and lithium metal is not ideal. During the lithium deposition process, lithium metal will gradually penetrate into the sulfide solid electrolyte, causing damage to the brittle electrolyte layer, resulting in unsatisfactory battery cycle life and rate capability. To solve the above problems, according to the fracture mechanics theory, sulfide solid electrolytes should have high ionic conductivity and high conductivity; the interface formed by the reaction of sulfide solid electrolytes and lithium metal should have high lithium diffusion capacity. In addition, considering the problem of interfacial voids during lithium stripping, the interface formed by the reaction of sulfide solid electrolytes and lithium metal should have high lithium affinity to reduce the contact loss between the phases. However, conventional solid-state electrolyte modification methods such as doping not only involve a tedious trial-and-error process, but also find it difficult to simultaneously optimize the multiple macroscopic properties required to effectively inhibit lithium intrusion as mentioned above.
[0004] Therefore, there is an urgent need to develop a large-scale method for modifying sulfide solid electrolytes to optimize the macroscopic properties of sulfide solid electrolytes from multiple dimensions, inhibit the invasion of lithium metal, and thus improve the cycle life and rate capability of the battery. Summary of the invention
[0005] The purpose of the present invention is to provide a method for improving the stability of sulfide electrolytes to lithium on a large scale. The composite sulfide electrolyte prepared by the method has the characteristics of high ionic conductivity and high density. After reacting with metallic lithium, a self-limited growth interface layer is generated, which can improve the diffusion rate of lithium in the interface. The prepared all-solid-state lithium metal battery has a long cycle life and excellent rate performance.
[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A method for improving the stability of sulfide electrolyte to lithium on a large scale, comprising: immersing the sulfide electrolyte in a liquid inorganic metal halide under the protection of an inert gas, standing at room temperature until the unreacted metal halide liquid volatilizes, obtaining composite sulfide electrolyte precursor particles, and mechanically compounding the composite sulfide electrolyte precursor particles with the sulfide electrolyte to obtain a composite sulfide electrolyte; wherein the sulfide electrolyte is Li 6-x-y PS 5-x-y Cl 1+x Br y , 0.3≤x<0.6, 0.1≤y<0.7; liquid inorganic metal halides include SnCl 4 、TiCl 4 、TiBr 4 The composite sulfide electrolyte combines electrolyte precursor particles coated with amorphous metal compound lithium chloride and sulfide electrolyte. It not only has high ionic conductivity and high density, but also has a self-limited growth interface layer with lithium-philic alloy components after reacting with metallic lithium, which can improve the diffusion rate of lithium in the interface and show extremely high stability to lithium.
[0007] Preferably, the mass ratio of the sulfide electrolyte to the liquid inorganic metal halide is 1-10:3-60.
[0008] Preferably, the mass ratio of the composite sulfide electrolyte precursor particles to the sulfide electrolyte is 1-10:2-50.
[0009] A composite positive electrode sheet is prepared from a sulfide electrolyte, a positive electrode active material, a conductive agent and a binder, wherein the positive electrode active material includes but is not limited to high-nickel ternary NCM83125, ternary NCM532, LiCoO 2; The binder includes but is not limited to polytetrafluoroethylene; The conductive agent includes but is not limited to acetylene black and sugar-based carbide; The preparation steps of sugar-based carbide are: mixing aniline with ammonium persulfate to prepare polyaniline; mixing cyclohexane hexaphosphate, 2-hydroxymethylimidazole, polyaniline and glucose to prepare a mixture; and carbonizing the mixture. Cyclohexane hexaphosphate, 2-hydroxymethylimidazole, polyaniline and glucose are carbonized together to form a multi-dimensional conductive network structure, which can provide more transmission paths for electrons, reduce the transmission impedance of electrons in electrode materials, accelerate the movement rate of electrons, and make sugar-based carbides have excellent conductivity and affinity for lithium ions, and the ability to improve the interface performance between electrodes and electrolytes, thereby effectively improving the stability of sulfide electrolytes to lithium in all-solid-state lithium metal batteries and the overall electrochemical performance of batteries.
[0010] Preferably, the mass ratio of aniline to ammonium persulfate is 1-5:1.6-8.
[0011] Preferably, the mass ratio of cyclohexanehexol hexaphosphate to glucose is 1-12:8-100.
[0012] Preferably, the mass ratio of 2-hydroxymethylimidazole to glucose is 1-15:6-100.
[0013] Preferably, the mass ratio of polyaniline to glucose is 1-15:6-100.
[0014] More preferably, 1,1,1-trifluoroacetylacetonate nickel can be added during the preparation of sugar-based carbides, and the mass ratio of 1,1,1-trifluoroacetylacetonate nickel to glucose is 1-12.5:8-100. 1,1,1-trifluoroacetylacetonate nickel can synergistically act with cyclohexanehexol hexaphosphate, 2-hydroxymethylimidazole and other substances to change the charge distribution or chemical environment inside the conductive agent, optimize the transmission path of lithium ions, and improve the rate performance of the battery; the formed electrode and electrolyte interface layer can regulate the deposition behavior of lithium ions at the interface, make lithium ions deposited evenly, inhibit the growth of lithium dendrites, and enhance the stability to lithium.
[0015] An all-solid-state lithium metal battery consists of an electrolyte material, a composite positive electrode plate and a negative electrode material, wherein the electrolyte material is a composite sulfide electrolyte.
[0016] Preferably, the negative electrode material includes, but is not limited to, lithium metal, lithium metal / carbon composite materials, and lithium silicon alloys. Any material suitable for use as a negative electrode material in the art can be used.
[0017] The present invention provides a method for preparing a composite sulfide electrolyte, comprising: Under the protection of inert gas, the sulfide electrolyte is immersed in liquid inorganic metal halide and allowed to stand at room temperature until unreacted metal halide liquid evaporates to obtain composite sulfide electrolyte precursor particles. The composite sulfide electrolyte precursor particles and the sulfide electrolyte are mechanically composited using a high-energy ball milling method. The grinding balls are zirconium dioxide balls with a diameter of 6-10 mm, the ball milling speed is 100-150 rpm, and the ball milling time is 3-15 min to obtain a composite sulfide electrolyte.
[0018] Preferably, the inert gas is one of argon and nitrogen.
[0019] More preferably, the inert gas is argon.
[0020] Preferably, the sulfide electrolyte is Li 6-x-y PS 5-x-y Cl 1+x Br y , where 0.3≤x<0.6, 0.1≤y<0.7.
[0021] Preferably, the liquid inorganic metal halide is SnCl 4 、TiCl 4 、TiBr 4 At least one of .
[0022] Preferably, the mass ratio of the sulfide electrolyte to the liquid inorganic metal halide is 1-10:3-60.
[0023] Preferably, the mass ratio of the composite sulfide electrolyte precursor particles to the sulfide electrolyte is 1-10:2-50.
[0024] Preferably, the quantity and mass ratio of the grinding balls to the sulfide electrolyte is 10-100:1-10 g.
[0025] The present invention provides a method for preparing a sugar-based carbide, comprising: Dissolve ammonium persulfate in deionized water to obtain an ammonium persulfate solution, dissolve aniline in deionized water under 0-4°C ice-water bath conditions to obtain an aniline solution, add the ammonium persulfate solution to the aniline solution under stirring conditions, stir for reaction for 4-6 hours, filter, wash the precipitate with deionized water and dry to obtain polyaniline. Mix cyclohexane hexaphosphate, 2-hydroxymethylimidazole, polyaniline and glucose, dissolve in deionized water, stir evenly to form a mixed dispersion, dry at 70-90°C and grind evenly to obtain a mixed powder, heat from room temperature to 550-650°C and maintain for 3-5 hours under nitrogen gas protection, heat to 850-950°C and maintain for 1-3 hours to obtain a sugar-based carbide.
[0026] Preferably, in the ammonium persulfate solution, the mass volume ratio of ammonium persulfate to deionized water is 2-12 g: 2.5-15 mL.
[0027] Preferably, the mass ratio of aniline to ammonium persulfate is 1-5:1.6-8.
[0028] Preferably, in the aniline solution, the mass volume ratio of aniline to deionized water is 1-5 g:24-120 mL.
[0029] Preferably, in the mixed dispersion, the mass ratio of cyclohexanehexol hexaphosphate to glucose is 1-12:8-100.
[0030] Preferably, in the mixed dispersion, the mass ratio of 2-hydroxymethylimidazole to glucose is 1-15:6-100.
[0031] Preferably, in the mixed dispersion, the mass ratio of polyaniline to glucose is 1-15:6-100.
[0032] Preferably, in the mixed dispersion, the mass volume ratio of glucose to deionized water is 5-50 g:25-250 mL.
[0033] The present invention provides a method for preparing a composite positive electrode sheet, comprising: The sulfide electrolyte, the positive electrode active material and the conductive agent are uniformly mixed, a binder is added and a shear force is applied to prepare a composite positive electrode sheet.
[0034] Preferably, the positive electrode active material includes but is not limited to high nickel ternary NCM83125, ternary NCM532, LiCoO 2 Any material suitable for use as a positive electrode material in the art can be used.
[0035] Preferably, the conductive agent includes but is not limited to acetylene black and sugar-based carbide, and any material suitable for being used as a conductive agent in the art can be used.
[0036] Preferably, the binder includes but is not limited to polytetrafluoroethylene, and any material suitable for use as a binder in the art can be used.
[0037] Preferably, the mass ratio of the sulfide electrolyte to the positive electrode active material is 26-30:70-74.
[0038] Preferably, the mass ratio of the conductive agent to the positive electrode active material is 1-5:140-740.
[0039] Preferably, the mass ratio of the binder to the positive electrode active material is 1-4:175-740.
[0040] The present invention provides a method for preparing an all-solid-state lithium metal battery, comprising: 60-100 mg of composite sulfide electrolyte is pressed into a 0.4-0.6 mm thick electrolyte sheet under a pressure of 500-700 MPa, the composite positive electrode sheet is placed on one side of the electrolyte sheet, and a pressure of 500-700 MPa is reapplied to ensure full contact between the positive electrode and the electrolyte, and lithium metal is placed on the other side of the electrolyte sheet to obtain an all-solid-state lithium metal battery.
[0041] Preferably, the negative electrode material includes, but is not limited to, lithium metal, lithium metal / carbon composite materials, and lithium silicon alloys. Any material suitable for use as a negative electrode material in the art can be used.
[0042] The present invention uses a composite sulfide electrolyte obtained by liquid-phase immersion and mechanical compounding of a sulfide electrolyte; and a sugar-based carbide formed by carbonization of cyclohexane hexol hexaphosphate, 2-hydroxymethylimidazole, polyaniline and glucose as a conductive agent, so it has the following beneficial effects: the composite sulfide electrolyte has high ionic conductivity and high density, improves the diffusion rate of lithium in the interface, and exhibits extremely high stability to lithium; the sugar-based carbide has excellent conductivity and affinity for lithium ions, and can improve the ability of the electrode and electrolyte interface performance, effectively improving the overall electrochemical performance of the battery. Therefore, the present invention is a method for large-scale improvement of the stability of sulfide electrolytes to lithium with high ionic conductivity, high exchange current density and long cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Schematic diagram of transmission electron microscopy of composite sulfide electrolyte precursor particles.
[0044] Figure 2 Schematic diagram of the scanning electron microscope of the electrolyte sheet.
[0045] Figure 3 Schematic diagram of the ionic conductivity test results of the electrolyte.
[0046] Figure 4 Schematic diagram of the exchange current density test results of lithium symmetric batteries.
[0047] Figure 5 Schematic diagram of the low-rate charge and discharge cycle test results of all-solid-state lithium batteries. DETAILED DESCRIPTION
[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.
[0050] Embodiment 1: Preparation of electrolyte materials: Under the protection of argon gas, sulfide electrolyte is immersed in liquid inorganic metal halide, and left to stand at room temperature until the unreacted metal halide liquid evaporates to obtain composite sulfide electrolyte precursor particles, and the composite sulfide electrolyte precursor particles are mechanically compounded with the sulfide electrolyte using a high-energy ball milling method to obtain a composite sulfide electrolyte. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 , the liquid inorganic metal halide is SnCl 4 , Li 5.5 PS 4.5 Cl 1.5 With SnCl 4 The mass ratio of the composite sulfide electrolyte precursor particles to Li 5.5 PS 4.5 Cl 1.5 The mass ratio of the grinding balls is 1:2, the grinding balls are zirconia balls with a diameter of 8 mm, the ball milling speed is 110 rpm, the ball milling time is 10 min, and the number mass ratio of the grinding balls to the sulfide electrolyte is 10:1 g.
[0051] Preparation of composite positive electrode sheet: sulfide electrolyte, positive electrode active material and conductive agent are mixed evenly, a binder is added and shear force is applied to prepare a composite positive electrode sheet. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The positive electrode active material is NCM83125, the conductive agent is acetylene black, the binder is polytetrafluoroethylene, the mass ratio of sulfide electrolyte to positive electrode active material is 28:72, the mass ratio of acetylene black to positive electrode active material is 0.5:72, and the mass ratio of polytetrafluoroethylene to positive electrode active material is 0.4:72.
[0052] Preparation of all-solid-state lithium metal battery: 80 mg of electrolyte material is pressed into a 0.5 mm thick electrolyte sheet under a pressure of 600 MPa, the composite positive electrode sheet is placed on one side of the electrolyte sheet, and a pressure of 600 MPa is reapplied to ensure full contact between the positive electrode and the electrolyte, and lithium metal is placed on the other side of the electrolyte sheet to obtain an all-solid-state lithium metal battery.
[0053] Example 2: Compared with Example 1, the difference between this example and this example is only the preparation of the composite positive electrode sheet.
[0054] Preparation of sugar-based carbide: dissolve ammonium persulfate in deionized water to obtain an ammonium persulfate solution, dissolve aniline in deionized water under 2°C ice-water bath conditions to obtain an aniline solution, add the ammonium persulfate solution to the aniline solution under stirring conditions, stir and react for 5 hours, filter, wash the precipitate with deionized water and dry to obtain polyaniline. Mix cyclohexane hexaphosphate, 2-hydroxymethylimidazole, polyaniline and glucose, dissolve in deionized water, stir evenly to form a mixed dispersion, dry at 80°C and grind evenly to obtain a mixed powder, heat from room temperature to 600°C and maintain for 4 hours under nitrogen gas protection, and heat to 900°C and maintain for 2 hours to obtain sugar-based carbide. In the ammonium persulfate solution, the mass volume ratio of ammonium persulfate to deionized water is 4g: 5mL; the mass ratio of aniline to ammonium persulfate is 2.5:4; in the aniline solution, the mass volume ratio of aniline to deionized water is 2.5g:60mL; in the mixed dispersion, the mass ratio of cyclohexanehexol hexaphosphate to glucose is 1.2:10, the mass ratio of 2-hydroxymethylimidazole to glucose is 1.5:10, the mass ratio of polyaniline to glucose is 1.5:10, and the mass volume ratio of glucose to deionized water is 10g:50mL.
[0055] Preparation of composite positive electrode sheet: sulfide electrolyte, positive electrode active material and conductive agent are mixed evenly, a binder is added and shear force is applied to prepare a composite positive electrode sheet. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The positive electrode active material is NCM83125, the binder is polytetrafluoroethylene, the conductive agent is sugar-based carbide, the mass ratio of sulfide electrolyte to positive electrode active material is 28:72, the mass ratio of sugar-based carbide to positive electrode active material is 0.5:72, and the mass ratio of polytetrafluoroethylene to positive electrode active material is 0.4:72.
[0056] Example 3: The difference between this example and Example 2 lies only in the preparation of sugar-based carbide.
[0057] Preparation of sugar-based carbide: dissolve ammonium persulfate in deionized water to obtain an ammonium persulfate solution, dissolve aniline in deionized water under 2°C ice-water bath conditions to obtain an aniline solution, add the ammonium persulfate solution to the aniline solution under stirring conditions, stir and react for 5 hours, filter, wash the precipitate with deionized water and dry to obtain polyaniline. Mix cyclohexane hexaphosphate, 2-hydroxymethylimidazole, polyaniline and glucose, dissolve in deionized water, stir evenly to form a mixed dispersion, dry at 80°C and grind evenly to obtain a mixed powder, heat from room temperature to 600°C and maintain for 4 hours under nitrogen gas protection, and heat to 900°C and maintain for 2 hours to obtain sugar-based carbide. In the ammonium persulfate solution, the mass volume ratio of ammonium persulfate to deionized water is 4g: 5mL; the mass ratio of aniline to ammonium persulfate is 2.5:4; in the aniline solution, the mass volume ratio of aniline to deionized water is 2.5g:60mL; in the mixed dispersion, the mass ratio of cyclohexanehexol hexaphosphate to glucose is 1.8:10, the mass ratio of 2-hydroxymethylimidazole to glucose is 1:10, the mass ratio of polyaniline to glucose is 1.5:10, and the mass volume ratio of glucose to deionized water is 10g:50mL.
[0058] Example 4: The difference between this example and Example 2 lies only in the preparation of sugar-based carbide.
[0059] Preparation of sugar-based carbide: dissolve ammonium persulfate in deionized water to obtain an ammonium persulfate solution, dissolve aniline in deionized water under 2°C ice-water bath conditions to obtain an aniline solution, add the ammonium persulfate solution to the aniline solution under stirring conditions, stir and react for 5 hours, filter, wash the precipitate with deionized water and dry to obtain polyaniline. Mix cyclohexane hexaphosphate, 2-hydroxymethylimidazole, polyaniline, 1,1,1-trifluoroacetylacetonate nickel and glucose, dissolve in deionized water, stir evenly to form a mixed dispersion, dry at 80°C and grind evenly to obtain a mixed powder, heat from room temperature to 600°C and maintain for 4 hours under nitrogen gas protection, and heat to 900°C and maintain for 2 hours to obtain sugar-based carbide. In the ammonium persulfate solution, the mass volume ratio of ammonium persulfate to deionized water is 4g:5mL; the mass ratio of aniline to ammonium persulfate is 2.5:4; in the aniline solution, the mass volume ratio of aniline to deionized water is 2.5g:60mL; in the mixed dispersion, the mass ratio of cyclohexanehexol hexaphosphate to glucose is 1.2:10, the mass ratio of 2-hydroxymethylimidazole to glucose is 1.5:10, the mass ratio of polyaniline to glucose is 1.5:10, the mass ratio of 1,1,1-trifluoroacetylacetonate nickel to glucose is 1.25:10, and the mass volume ratio of glucose to deionized water is 10g:50mL.
[0060] Example 5: The difference between this example and Example 2 lies only in the preparation of sugar-based carbide.
[0061] Preparation of sugar-based carbide: dissolve ammonium persulfate in deionized water to obtain an ammonium persulfate solution, dissolve aniline in deionized water under 2°C ice-water bath conditions to obtain an aniline solution, add the ammonium persulfate solution to the aniline solution under stirring conditions, stir and react for 5 hours, filter, wash the precipitate with deionized water and dry to obtain polyaniline. Mix cyclohexane hexaphosphate, 2-hydroxymethylimidazole, polyaniline, 1,1,1-trifluoroacetylacetonate nickel and glucose, dissolve in deionized water, stir evenly to form a mixed dispersion, dry at 80°C and grind evenly to obtain a mixed powder, heat from room temperature to 600°C and maintain for 4 hours under nitrogen gas protection, and heat to 900°C and maintain for 2 hours to obtain sugar-based carbide. In the ammonium persulfate solution, the mass volume ratio of ammonium persulfate to deionized water is 4g: 5mL; the mass ratio of aniline to ammonium persulfate is 2.5:4; in the aniline solution, the mass volume ratio of aniline to deionized water is 2.5g:60mL; in the mixed dispersion, the mass ratio of cyclohexanehexol hexaphosphate to glucose is 1.2:10, the mass ratio of 2-hydroxymethylimidazole to glucose is 1.5:10, the mass ratio of polyaniline to glucose is 1.5:10, the mass ratio of 1,1,1-trifluoroacetylacetonate nickel to glucose is 2.5:10, and the mass volume ratio of glucose to deionized water is 10g:50mL.
[0062] Comparative Example 1: Compared with Example 1, the difference between this comparative example and Example 1 lies only in the preparation of the electrolyte material.
[0063] Preparation of electrolyte materials: Sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 As electrolyte material.
[0064] Comparative Example 2: Compared with Example 1, the difference between this comparative example and Example 1 lies only in the preparation of the electrolyte material.
[0065] Preparation of electrolyte materials: Under the protection of argon gas, sulfide electrolyte is immersed in liquid inorganic metal halide, and left to stand at room temperature until the unreacted metal halide liquid evaporates, thereby obtaining composite sulfide electrolyte precursor particles as electrolyte materials. The sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 , the liquid inorganic metal halide is SnCl 4 , Li 5.5 PS 4.5 Cl 1.5 With SnCl 4 The mass ratio is 1:4.
[0066] Comparative Example 3: This comparative example is different from Example 2 only in that cyclohexanehexol hexaphosphate is not used in the preparation of the sugar-based carbide.
[0067] Comparative Example 4: This comparative example is different from Example 2 only in that 2-hydroxymethylimidazole is not used in the preparation of the sugar-based carbide.
[0068] Comparative Example 5: This comparative example is different from Example 2 only in that cyclohexanehexol hexaphosphate and 2-hydroxymethylimidazole are not used in the preparation of the sugar-based carbide.
[0069] Experimental Example 1: Microstructural characterization of composite sulfide electrolyte precursor particles.
[0070] Test sample: the composite sulfide electrolyte precursor particles prepared in Example 1.
[0071] Test method: The composite sulfide electrolyte precursor particles are scanned by transmission electron microscopy to obtain the microstructural characteristics of the sample.
[0072] The transmission electron microscope image of the composite sulfide electrolyte precursor particles prepared by the present invention is as follows: Figure 1 As shown, it shows that the composite sulfide electrolyte precursor particles as shown in the figure are successfully obtained. Figure 1 (a) is a transmission electron micrograph of the composite sulfide electrolyte precursor particles prepared in Example 1; Figure 1 (b) shows the distribution of sulfur in the composite sulfide electrolyte precursor particles; Figure 1 (c) is the distribution of chlorine in the composite sulfide electrolyte precursor particles; Figure 1 (d) is the distribution of tin element in the composite sulfide electrolyte precursor particles; Figure 1 (e) High-resolution transmission electron microscopy observation results of the outer layer of the composite sulfide electrolyte precursor particles.
[0073] Experimental Example 2: Microstructural characterization of electrolyte sheets.
[0074] Test samples: electrolyte materials prepared in Example 1, Comparative Example 1 and Comparative Example 2.
[0075] Test method: 150 mg of the electrolyte material prepared in Example 1 was pressed into a thin sheet of approximately 1.135 mm at a pressure of 600 MPa, 150 mg of the electrolyte material prepared in Comparative Example 1 was pressed into a thin sheet of approximately 1.259 mm at a pressure of 600 MPa, and 150 mg of the electrolyte material prepared in Comparative Example 2 was pressed into a thin sheet of approximately 0.936 mm at a pressure of 600 MPa, and the surface defect density of the samples was observed using a scanning electron microscope.
[0076] The scanning electron microscope image of the electrolyte sheet prepared by the present invention is as follows: Figure 2 As shown, Figure 2 (a) Figure 2 (b) Figure 2(c) are the results of Example 1, Comparative Example 1, and Comparative Example 2, respectively. Figure 2 (b) It can be seen that Li in Comparative Example 1 5.5 PS 4.5 Cl 1.5 The electrolyte has a polycrystalline grain boundary, which leads to the non-dense stacking of grains during the cold pressing process, resulting in a large number of defects on its surface. Figure 2 (c) It can be seen that the electrolyte precursor particles prepared in Comparative Example 2 after liquid phase infiltration have a large amount of amorphous compounds on the surface, and the electrolyte sheet formed by the stacking is very dense, and almost no obvious surface defects are observed; Figure 2 (a) It can be seen that the composite sulfide electrolyte powder material prepared in Example 1 retains the advantages of the electrolyte precursor particles treated by liquid phase infiltration, and the electrolyte sheet formed by stacking its particles is still dense.
[0077] Test Example 3: Ion conductivity test of electrolyte sheet.
[0078] Test samples: electrolyte materials prepared in Example 1, Comparative Example 1 and Comparative Example 2.
[0079] Test method: 150 mg of the electrolyte material prepared in Example 1 was pressed into a thin sheet of approximately 1.135 mm at a pressure of 600 MPa, 150 mg of the electrolyte material prepared in Comparative Example 1 was pressed into a thin sheet of approximately 1.259 mm at a pressure of 600 MPa, and 150 mg of the electrolyte material prepared in Comparative Example 2 was pressed into a thin sheet of approximately 0.936 mm at a pressure of 600 MPa. Carbon-coated aluminum foils were fixed on both sides of the electrolyte sheet to form a sandwich structure, and its AC impedance spectrum was obtained by an electrochemical workstation, and the ionic conductivity was calculated.
[0080] The ionic conductivity test results of the electrolyte prepared by the present invention are as follows: Figure 3 As shown, Figure 3 (a) is the AC impedance diagram of the blocked battery of the electrolyte in Example 1, and the ionic conductivity is 6.2 mS / cm; Figure 3 (b) is the AC impedance diagram of the blocked battery of the electrolyte in Comparative Example 1, and the ionic conductivity is 7.4 mS / cm; Figure 3 (c) is the AC impedance diagram of the blocked battery with electrolyte in Comparative Example 2, and the ionic conductivity is 4.8 mS / cm. Compared with Comparative Examples 1-2, it can be seen that the liquid phase infiltration modification process can significantly reduce the original Li 5.5 PS 4.5 Cl 1.5 The ionic conductivity of the electrolyte, after the mechanical compounding step, the original Li 5.5 PS 4.5 Cl 1.5The high ionic conductivity property of the electrolyte is retained in the developed composite sulfide electrolyte.
[0081] Test Example 4: Exchange current density test of lithium symmetric battery Test samples: electrolyte materials prepared in Example 1, Comparative Example 1 and Comparative Example 2.
[0082] Test method: 150 mg of electrolyte material was pressed into an electrolyte sheet under a pressure of 600 MPa, lithium metal electrodes were attached to both sides of the electrolyte sheet to obtain a lithium symmetrical battery, and an electrochemical workstation was connected. The frequency range of 10 mHz-1 MHz and the amplitude of 5-10 mV were set to perform AC impedance test to obtain the exchange current density.
[0083] The exchange current density test results of the lithium symmetrical battery prepared by the present invention are as follows: Figure 4 ,Depend on Figure 4 (a) It can be seen that the exchange current density of Example 1 is 1.37 mA / cm 2 ;Depend on Figure 4 (b) It can be seen that the exchange current density of Comparative Example 1 is 1.06 mA / cm 2 ,Depend on Figure 4 (c) It can be seen that the exchange current density of Comparative Example 2 is 0.6 mA / cm 2 Compared with Comparative Examples 1-2, Example 1 shows that although the reaction of the electrolyte modified by liquid phase infiltration with metallic lithium can generate a self-limiting interface containing a lithium-philic alloy, due to the low ionic conductivity of the electrolyte modified by liquid phase infiltration, its symmetric battery exchange current density is lower than that of the original Li 5.5 PS 4.5 Cl 1.5 The symmetric battery exchange current density of the electrolyte is high, and the composite sulfide electrolyte obtained by mechanical compounding can generate a self-limiting interface containing a lithium-philic alloy to increase the diffusion rate of lithium in the interface, and the constructed symmetric battery has a higher lithium symmetric battery exchange current value.
[0084] Experimental Example 5: Critical current density test of lithium symmetric battery.
[0085] Test samples: electrolyte materials prepared in Example 1, Comparative Example 1 and Comparative Example 2.
[0086] Test method: 150 mg of electrolyte material is pressed into an electrolyte sheet under a pressure of 600 MPa, and lithium metal electrodes are attached to both sides of the electrolyte sheet to obtain a lithium symmetrical battery. The battery is connected to an electrochemical workstation, and a cyclic charge and discharge test is performed at a test temperature of 25°C by gradually increasing the constant current density until the battery reaches a critical state of short circuit, and the critical current density is obtained.
[0087] The critical current density of Example 1 is 2.8 mA / cm2 The critical current density of comparative example 1 is 1.0 mA / cm 2 The critical current density of comparative example 2 is 1.8 mA / cm 2 Compared with Comparative Examples 1-2, Example 1 shows that the composite sulfide electrolyte obtained by liquid phase infiltration and mechanical compounding can exert high stability to lithium, and the prepared lithium symmetric battery has a very high critical current density.
[0088] Test Example 6: Full-cell low-rate charge and discharge cycle test of an all-solid-state lithium battery.
[0089] Test samples: all-solid-state lithium batteries prepared by the methods of various embodiments and comparative examples.
[0090] Test method: Use a charge and discharge tester with a charge and discharge voltage range of 2.5-4.25V, a charge and discharge rate of 0.1C, and a test temperature of 25°C to perform an initial charge and discharge test and calculate the capacity retention rate after 50 cycles.
[0091] The capacity retention rate test results of the all-solid-state lithium battery prepared by the present invention are as follows Figure 5 As shown, the capacity retention rate of Example 1 is 85.2%, the capacity retention rate of Example 2 is 88.8%, the capacity retention rate of Example 3 is 90.0%, the capacity retention rate of Example 4 is 92.1%, and the capacity retention rate of Example 5 is 92.8%. It can be seen from Examples 1-5 that with the optimization of the conductive agent structure and the improvement of the preparation process, the cycle stability of the battery is significantly improved, indicating that the sugar-based carbide used in Examples 2 and 3 can improve the interface performance between the electrode and the electrolyte, reduce capacity loss, and extend the battery cycle life. After adding 1,1,1-trifluoroacetylacetonate nickel to Examples 4 and 5, the capacity retention rate is improved, indicating that its synergistic effect with other substances can effectively inhibit the growth of lithium dendrites, reduce the loss of active substances, and thus improve the cycle stability of the battery. The capacity retention rate of Comparative Example 1 is 70.5%, the capacity retention rate of Comparative Example 2 is 78.7%, the capacity retention rate of Comparative Example 3 is 83.2%, the capacity retention rate of Comparative Example 4 is 84.0%, and the capacity retention rate of Comparative Example 5 is 80.1%, indicating that the composite sulfide electrolyte preparation method and the mechanical composite step of the present invention play an important role in improving the battery cycle stability. At the same time, cyclohexanehexanol hexaphosphate and 2-hydroxymethylimidazole play an important role in improving the battery cycle performance. The lack of them will lead to a decrease in the battery capacity retention rate and poor cycle stability.
[0092] Test Example 7: Full-cell high-rate charge and discharge cycle test of an all-solid-state lithium battery.
[0093] Test samples: all-solid-state lithium batteries prepared by the methods of various embodiments and comparative examples.
[0094] Test method: Use a charge and discharge tester with a charge and discharge voltage range of 2.5-4.25V, a charge and discharge rate of 0.5C and 1C, and a test temperature of 25°C to perform a charge and discharge cycle test. Record the capacity retention rate after 1000 cycles at a 0.5C discharge rate and the capacity retention rate after 2000 cycles at a 1C discharge rate.
[0095] The capacity retention rate test results of the all-solid-state lithium battery prepared by the present invention are shown in Table 1: Table 1 Capacity retention test results of all-solid-state lithium batteries
[0096] From the analysis of Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the composite sulfide electrolyte powder material modified and developed by Example 1 is better than the original Li 5.5 PS 4.5 Cl 1.5 Electrolyte and liquid-only infiltration modified Li 5.5 PS 4.5 Cl 1.5 The electrolyte shows excellent performance in the full-battery high-rate charge and discharge cycle test. In particular, the all-solid-state lithium metal battery assembled with the composite sulfide electrolyte modified and developed in Example 1 can cycle more than 2000 times at a rate of 1C, and the capacity retention rate is 93%. The extremely high lithium stability of the composite sulfide electrolyte can be attributed to its following multi-dimensional optimized macroscopic properties: high ionic conductivity and high density; after reacting with metallic lithium, it has a lithium-philic alloy component, which improves the diffusion rate of lithium at the interface. And Examples 2-5 optimize the sugar-based carbide. Compared with Example 1, the full-battery high-rate charge and discharge cycle test performance is also improved. Compared with Comparative Examples 3-5, the capacity retention rate is more significantly increased, indicating that with the optimization of the conductive agent structure and the improvement of the preparation process, the prepared pole piece can effectively inhibit the growth of lithium dendrites and reduce the loss of active substances, thereby improving the cycle stability of the battery.
[0097] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.
[0098] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the invention to other occasions without improvement, should be regarded as the scope of protection of this application.
Claims
1. A method for improving the stability of sulfide electrolytes to lithium on a large scale, comprising: Under the protection of an inert gas, a sulfide electrolyte is immersed in a liquid inorganic metal halide, and allowed to stand at room temperature until the unreacted metal halide liquid evaporates to obtain composite sulfide electrolyte precursor particles, and the composite sulfide electrolyte precursor particles are mechanically composited with the sulfide electrolyte to obtain a composite sulfide electrolyte; wherein the sulfide electrolyte is Li 6-x-y PS 5-x-y Cl 1+x Br y , 0.3≤x<0.6, 0.1≤y<0.7; the liquid inorganic metal halide includes at least one of SnCl4, TiCl4, and TiBr4.
2. A method for improving the stability of sulfide electrolytes to lithium on a large scale according to claim 1, characterized in that: The mass ratio of the sulfide electrolyte to the liquid inorganic metal halide is 1-10:3-60.
3. A method for improving the stability of sulfide electrolytes to lithium on a large scale according to claim 1, characterized in that: The mass ratio of the composite sulfide electrolyte precursor particles to the sulfide electrolyte is 1-10:2-50.
4. A composite positive electrode sheet, prepared from a sulfide electrolyte, a positive electrode active material, a conductive agent and a binder, characterized in that: The positive electrode active material includes but is not limited to high-nickel ternary NCM83125, ternary NCM532, and LiCoO2; the binder includes but is not limited to polytetrafluoroethylene; the conductive agent includes but is not limited to acetylene black and sugar-based carbide; wherein the preparation steps of the sugar-based carbide are: mixing aniline with ammonium persulfate to prepare polyaniline; mixing cyclohexanehexol hexaphosphate, 2-hydroxymethylimidazole, polyaniline and glucose to prepare a mixture; and carbonizing the mixture to obtain sugar-based carbide.
5. A composite positive electrode sheet according to claim 4, characterized in that: The mass ratio of aniline to ammonium persulfate is 1-5:1.6-8.
6. A composite positive electrode sheet according to claim 4, characterized in that: The mass ratio of cyclohexanehexol hexaphosphate to glucose is 1-12:8-100, the mass ratio of 2-hydroxymethylimidazole to glucose is 1-15:6-100, and the mass ratio of polyaniline to glucose is 1-15:6-100.
7. A composite positive electrode sheet according to claim 4, characterized in that: The carbonization treatment is carried out at 550-950°C.
8. An all-solid-state lithium metal battery, consisting of an electrolyte material, a composite positive electrode plate and a negative electrode material, wherein the electrolyte material is a composite sulfide electrolyte, and the negative electrode material includes but is not limited to lithium metal, lithium metal / carbon composite material, and lithium silicon alloy.
9. Use of the all-solid-state lithium metal battery according to claim 8 in the preparation of vehicles.
Citation Information
Patent Citations
Stable lithium metal negative electrode
CN108428858A
Li3PS4 solid electrolyte, solid mixed electrolyte, all-solid-state lithium-sulfur battery and production method thereof
CN112397775A
Passivation layer sulfide solid electrolyte and preparation method and application thereof
CN114388803A
Solid-state battery cell, preparation method thereof and solid-state battery
CN117497835A
Surface layer doped sulfide solid electrolyte and preparation method and application thereof
CN118610562A